PENYULUHAN LITERASI KEUANGAN SEJAK DINI DI TK GEMA NURANI PEJUANG BEKASI - Yusbardini; Darryl (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
Education is an important investment for a child's future. Not only moral and academic education is needed, but also education on financial management. Lack of parental awareness about the importance of financial education from an early age, causes a child's lack of money management knowledge. The purpose of this Community Service (PKM) is to increase children's awareness from an early age so that they can get used to saving so they are able to manage finances, distinguish between wants and needs. Financial literacy counseling is carried out using an online method using Zoom Metting to parents of students (PAUD Group) TKIT Gema Nurani. Counseling was carried out in two meetings. The first is with Gema Conscience TKIT teachers and the second is with the parents of TKIT Gema Conscience students. Approach and Cooperation with Related Parties. This financial literacy education was successful. Furthermore, the application of financial literacy from an early age requires joint participation between teachers, parents and the PKM team so that they can increase knowledge of financial literacy from an early age and can provide benefits for kindergarten students.